Numerical solution of the stagnation point flow and heat transfer with several effects - Hasmawani, Hashim (2020)
Problems related to boundary layer flow and heat transfer is important due to its various practical applications in engineering and industrial area. Cooling systems, nuclear reactor, electronic, hydrodynamics process, paper production and the boundary layer in liquid film condensation process are some of the example of various applications related to boundary layer flow and heat transfer. Present thesis solved numerically three problems of boundary layer flow on stagnation point over a stretching by considering the Newtonian fluid (viscous fluid) and non-Newtonian fluid (Williamson fluid). Besides, this thesis concern of the influence of slip flow, thermal radiation, magnetohydrodynamic (MHD) and viscous dissipation effects associated with constant wall temperature as boundary conditions. All gorvening equations in the form partial differential equations are transformed into ordinary differential equations by employing the suitable similarity transformation. The transformed ordinary differential equations obtained are solved numerically using a Shooting method in Maple software. Numerical solutions are obtained for the local Nusselt number and skin friction coefficient as well as the temperature and velocity profiles. The features of the flow and heat transfer characteristics for various values of eight pertinent parameters which are the Prandtl number, the stretching parameter, the Eckert number, the velocity slip parameter, the thermal slip parameter, the radiation parameter, the magnetic parameter and the nonNewtonian Williamson fluid parameter are analyzed and discussed. The comparison is also done by verifying through existing research so that the results obtained are a good agreement and reliable. As conclusion, the increases of Prandtl number, stretching parameter, dimensionless thermal and velocity slip parameter result to the decreasing in the wall temperature and also thermal boundary layer thickness. Meanwhile, increasing the non-Newtonian Williamson fluid parameter and thermal radiation parameter, the thermal boundary layer also increases.